2011
DOI: 10.1056/nejmoa1000446
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Vaccine and Health Care Utilization for Diarrhea in U.S. Children

Abstract: Since the introduction of rotavirus vaccine, diarrhea-associated health care utilization and medical expenditures for U.S. children have decreased substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 16 publications
3
112
0
4
Order By: Relevance
“…RV5 and RV1 were recommended for routine vaccination of US infants in 2006 and 2008, respectively, 4 and their use has resulted in an annual decline of ∼40 000 gastroenteritis hospitalizations in 2008 and 2009 in US children, with an annual reduction of about $140 million in treatment costs. 5 Recent postlicensure studies from Australia and Mexico have demonstrated a transient increased risk of intussusception during the first week after the first dose of both RV5 and RV1, at an estimated excess risk of ∼1 to 2 cases per 100 000 vaccinated infants. 6,7 Postlicensure studies in the United States have not documented an increased risk of intussusception with RV5, but available data are insufficient to confidently exclude a risk as small as seen in international settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RV5 and RV1 were recommended for routine vaccination of US infants in 2006 and 2008, respectively, 4 and their use has resulted in an annual decline of ∼40 000 gastroenteritis hospitalizations in 2008 and 2009 in US children, with an annual reduction of about $140 million in treatment costs. 5 Recent postlicensure studies from Australia and Mexico have demonstrated a transient increased risk of intussusception during the first week after the first dose of both RV5 and RV1, at an estimated excess risk of ∼1 to 2 cases per 100 000 vaccinated infants. 6,7 Postlicensure studies in the United States have not documented an increased risk of intussusception with RV5, but available data are insufficient to confidently exclude a risk as small as seen in international settings.…”
Section: Discussionmentioning
confidence: 99%
“…This is substantially lower than the number of diarrhea hospitalizations prevented annually (∼40 000) since rotavirus vaccine introduction. 5,23 …”
Section: Figurementioning
confidence: 99%
“…The MarketScan commercial database is representative of the commercially insured population in the United States and has been published widely in a variety of therapeutic areas focusing on epidemiology and outcomes research. 22,23 The MarketScan commercial database used in this study is de-identified and fully compliant with the Health Insurance Portability and Accountability Act of 1996; thus, this study was exempt from the review and approval of an institutional review board.…”
Section: ■■ Methodsmentioning
confidence: 99%
“…RV vaccines are highly effective, with efficacy between 57% and 87% against severe RV-associated diarrhea, and higher efficacy in industrialized countries [3]. Since vaccine introduction, hospitalization rates due to RV gastroenteritis in children under 5 years have decreased by 65-84% in Europe, in Australia by 71%, and in the USA by 60-75% [4][5][6]. However, RV vaccines remain underutilized globally -as of April 2016, only 85 countries (44%) included routine vaccination in their national program (http://www.who.int/immunization/monitoring_surveillance/ data/en/, accessed 5 May 2016).…”
Section: The Impact Of Rv Vaccine Introductionmentioning
confidence: 99%